Covert hepatic encephalopathy leads to distinct alterations in the emotional state, independently of MELD-Score - Greinert, Robin; Ripoll, Cristina; Zipprich, Alexander (Zeitschrift für Gastroenterologie, 2018)
Background and aims Covert hepatic encephalopathy impairs many aspects of quality of life, although its impact on the emotional state has not been evaluated. This study aims to evaluate the impact of covert hepatic encephalopathy on the emotional state and which factors are associated with changes in the emotional state in patients with cirrhosis.Methods This single-center study included all patients with cirrhosis who underwent the portosystemic encephalopathy syndrome (PSE) test, critical flicker frequency, and emotional state assessment with the Eigenschaftswörterliste 60-S in 2011. Covert hepatic encephalopathy was defined by abnormal PSE. Parametric and non-parametric tests were used according to variable distribution.Results One hundred seventeen patients with cirrhosis were included (median age: 59 [interquartile range: 48 – 67], 32 % female, 74 % alcohol-associated). Seventy patients had covert hepatic encephalopathy (60 %) with a higher MELD (16 [interquartile range: 13 – 21], p = 0.001) and a higher Child-Pugh score (p = 0.003) compared to patients without encephalopathy. Patients with covert encephalopathy felt reduced mental activity (p = 0.004), lower general well-being (p = 0.001), and reduced extraversion (p = 0.021). The scores in the negative domains such as general lethargy (p = 0.031) and anxiousness/depressiveness (p = 0.033) were higher in patients with covert hepatic encephalopathy. There was no correlation between MELD and the emotional state. Patients with 2 pathological tests (critical flicker frequency and PSE) showed the most distinct alterations in the emotional state in the group of patients with covert hepatic encephalopathy.Conclusions Patients with covert hepatic encephalopathy have an alteration of the emotional state, which is more marked in patients with 2 pathological tests. Interestingly, MELD had no impact on the emotional state.
Keywords: hepatic encephalopathy; cirrhosis; quality of life; diagnosis